Parasitic and Ecological Factors Associated with Transmission of Urogenital Schistosomiasis in Owena Reservoir Area, Ondo State, Nigeria (World Journal of Current Medical and Pharmaceutical Research, 2023)
Human urogenital schistosomiasis caused by infection of the trematode worm Schistosoma hematobium is a major source of morbidity and mortality in Ondo State especially in Owena Reservoir Area, Ondo East Local Government Area, Ondo State, Nigeria. The aim of this study was to investigate: (i) the seasonal and spatial distribution, infection and cercariae shedding patterns of identified local Schistosoma intermediate snail host(s); (ii) to determine the influence of ecological factors on the identified intermediate snail species in the transmission of urogenital schistosomiasis along the Owena Reservoir and river courses. All the snails collected were placed in pre-labeled plastic containers and were transported to a Malacology Laboratory at Ile-Ife, Osun State, Nigeria. The snails were identified to species level, counted and recorded as number of snails, per site, per date. The snails were identified using standard identification keys. Examination of snails for Schistosoma infection was carried out by crushing method. Cercariae were identified to genus level. However, only snails shedding Schistosoma cercariae were recorded as infected. Each of the eight sites was sampled once monthly for twenty-four months. Eight stations (sites) of diverse ecological characteristics were selected along the Owena Reservoir and monitored for snails species’ diversity, distribution and infection patterns, physicochemical properties of H2O, macrophyte types and coverage in relation to the transmission of urogenital schistosomiasis. Seven snail species representing two sub-classes, three families and five genera were identified in Owena Reservoir Area. Bulinus globosus and Bulinus truncatus were the only established Schistosoma intermediate snail hosts in site 4 (KAJ 1) located in Kajola community. Out of the eight sites studied, site 4 in Kajola community had the highest infection rate while Embankment/Dam (site 8) had the least. Site 4 in Kajola community is therefore the major transmission site. All the snail species correlated positively with alkalinity conduction, negatively with air temperature. Bulinus globosus correlated significantly positive with Ludwiga erecta, Ludwiga decurrens, Commelina africana, and Berberis calamus (p0.05). Bulinus truncatus correlated significantly positive with Aspillia africana, Ludwiga decurrens, Emilia occinina, and Crosus sativue (p0.05). This study recommends environmental management and manipulation using water level regulations to render water contact sites environmentally unfriendly for both snail growth and human recreational activities during the period of high risk transmission since chemical control (the use of molluscicide) poses a risk to health, not only to the snail intermediate hosts but also to the inhabitants of the communities who commonly depend on reservoirs, streams, rivers, dams for their domestic water supply.